Case Report: Pituitary Morphology and Function Are Preserved in Female Patients With Idiopathic Intracranial Hypertension Under Pharmacological Treatment - Tozzi, Rossella; Moramarco, Antonietta; Watanabe, Mikiko; Balena, Angela; Caputi, Alessandra; Gangitano, Elena; Petrangeli, Elisa; Mariani, Stefania; Gnessi, Lucio; Lubrano, Carla (Frontiers in Endocrinology, 2021)
Idiopathic Intracranial Hypertension (IIH) is a neurological disorder typical of pediatric age often characterized by radiologic evidence of empty sella (ES), which is often associated with pituitary dysfunction, regarding the somatotropic axis mostly. No recent evidence relative to endocrinological complications is available in adult patients under pharmacological therapy. We therefore explored pituitary function and morphology in a small cohort of female patients with IIH treated with acetazolamide. Fifteen female patients with IIH lasting between 12 and 18 months were evaluated. All patients were affected from recurrent headaches in addition to varying severity visual changes and IIH diagnosis was made after exclusion of other causes of raised intracranial pressure and a specific ophtalmological evaluation was conducted for papilledema recording. No particular endocrinological disturbances were detected during the enrollment visits, except for high obesity prevalence (87%, BMI 35.16 ± 8.21 kg/m2), one case of total thyroidectomy for papillary thyroid carcinoma and two patients with irregular menses and mild hirsutism. All the participants underwent a pituitary MRI with contrast, and two different operators performed pituitary measurements in coronal and sagittal scans for morphologic assessment. Blood samples for the anterior pituitary axis evaluation were collected and somatotropic axis were better evaluated with GHRH + Arginine test; other dynamic tests were performed in case of suspected hormonal deficiency. Despite ES was found in 73% of the patients, pituitary volume was preserved ,ranging from 213.85 to 642.27mm3 (389.20 ± 125.53mm3); mean coronal pituitary height was 4.53 ± 1.33 mm. Overall, the basal anterior pituitary hormones levels were within the normal values except one patient suffering from iatrogenic hyperthyroidism and two subclinical primary hypothyroidism due to Hashimoto’s Thyroiditis. Two young patients were diagnosticated for PCOS. Of note, none of the ES patients had an altered response to GHRH + arginine stimulation test. These case series shows that, despite the high prevalence of ES, the pituitary function of IIH patients treated with acetazolamide is preserved. Since hormonal deficiencies may develop in IIH patients over time, an endocrinological follow-up is suggested.